MANAJEMEN PERPUSTAKAAN KHUSUS (STUDI DI PERPUSTAKAAN KEJAKSAAN NEGERI DENPASAR) - Mirayanti, Putu Ester; Haryanti, Ni Putu Premierita; Suhartika, I Putu (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2024)
A special library is a type of library intended for a specific agency or organization. The special library of the State Prosecutor's Office plays an important role in providing information and knowledge to the prosecution's employees. This research aims to examine the management system of the State Prosecutor's Office Library in Denpasar. The research method uses a qualitative approach with data collection techniques from observation, interviews, and documentation. The research results indicate that the management activities at the State Prosecutor's Office Library in Denpasar have not yet operated optimally and cannot be considered an ideal special library. This is because many management activities in the library do not comply with National Library Regulation No. 7 of 2022, which governs the specific standards for special libraries.